ANALYZING THE EFFECT OF PERCEIVED PRICE AND CUSTOMER TRUST ON CUSTOMER LOYALTY OF EYELASH EXTENSION SERVICE STUDY ON BEAUTY C LOUNGE MANADO - Mawuntu, Fransiska X. S.; Lapian, Joyce S.L.H.V; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2021)
Appearance is included in the list of important things for society today, especially for women. Appearance is also believed to improve confidence. Therefore many women are willing to spend their time and money on beauty treatments for example eyelash extensions. This research is conducted in Beauty C lounge (Star Square Manado, Ground Floor). The objectives of this research are to analyze the effects of perceived price and customer trust on customer loyalty, partially and simultaneously.Â This research is the causal type of research where it investigates the influence of perceived price and customer trust on customer loyalty. Using a multiple regression model to answer the research problem. The population in this study is a customer of Beauty C lounge with 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant effect of perceived price and customer trust on customer loyalty partially and simultaneously. This study reveals that perceived price and customer trust have a strong influence on the customer in order to use product and service and to be a loyal customer at Beauty C Lounge.Â Keywords: perceived price, customer trust, customer loyalty